2021
DOI: 10.1155/2021/2537546
|View full text |Cite
|
Sign up to set email alerts
|

Signal Modulation Recognition Method Based on Differential Privacy Federated Learning

Abstract: Signal modulation recognition is widely utilized in the field of spectrum detection, channel estimation, and interference recognition. With the development of artificial intelligence, substantial advances in signal recognition utilizing deep learning approaches have been achieved. However, a huge amount of data is required for deep learning. With increasing focus on privacy and security, barriers between data sources are sometimes difficult to break. This limits the data and renders them weak, so that deep lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…As these studies point out, CentAMR poses a significant privacy risk due to the extensive data transfer to the central server for model training. 2,5,26,27 However, it is worth noting that this challenge may not be as significant in wireless networks where signals are accessible. A study by Shi et al 27 explores federated learning-based AMR with differential privacy, specifically concentrating on data privacy in AMR tasks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As these studies point out, CentAMR poses a significant privacy risk due to the extensive data transfer to the central server for model training. 2,5,26,27 However, it is worth noting that this challenge may not be as significant in wireless networks where signals are accessible. A study by Shi et al 27 explores federated learning-based AMR with differential privacy, specifically concentrating on data privacy in AMR tasks.…”
Section: Related Workmentioning
confidence: 99%
“…2,5,26,27 However, it is worth noting that this challenge may not be as significant in wireless networks where signals are accessible. A study by Shi et al 27 explores federated learning-based AMR with differential privacy, specifically concentrating on data privacy in AMR tasks. They show that their achieved accuracy is acceptable compared to the centralized model, while ensuring data security.…”
Section: Related Workmentioning
confidence: 99%
“…A CNN-based federated learning approach was proposed in ref. [100], enabling differential privacy for modulation recognition in order to assure the privacy and security of transmitted data.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…The authors found that DL algorithms perform modulation recognition more accurately compared to ML algorithms such as the Support Vector Machine (SVM). To ensure the privacy and security of the transmitted data, Shi et al [ 46 ] proposed a CNN-based federated learning approach with differential privacy for modulation recognition.…”
Section: Artificial Intelligence (Ai)-enabled 6g Networkmentioning
confidence: 99%